Effects of graphene addition on mechanical properties of polycrystalline diamond compact. Issue 8 (1st June 2020) - Chen, Zhaoran; Ma, Dejiang; Wang, Shanmin; Dai, Wenhao; Li, Siqi; Zhu, Yiqing; Liu, Baochang
Abstract: Polycrystalline diamond compact (PDC) cutters are used widely for mining and drilling in soft to medium hard rock formations. During drilling in very hard and strong rock formations, the rapid wear of the polycrystalline diamond layer results in a low service life of drilling bits. To improve the performance of PDC cutters, we adopted a high-temperature, high-pressure (HTHP) sintering method (5.5–6.0 GPa and 1350–1500 °C) in the current research by adding a certain amount of graphene to raw materials, and we successfully prepared a new type of high-performance diamond composite PDC-G (graphene was added to PDC). We investigated the microstructure, residual stress, hardness, wear resistance, thermal conductivity, and electrical conductivity of the as-synthesized PDC-G. Compared with PDC without graphene, the hardness and wear resistance of PDC-G with 0.1 wt% graphene addition were enhanced by 75% and 33%, respectively. Moreover, the electrical conductivity of PDC prepared by graphene strengthening was improved 42-fold. The strengthening mechanism of PDC-G mainly occurred as a result of the lubricating effect of graphene between diamond particles; hence, a more dense and uniform structure was formed in the polycrystalline diamond layer after HTHP sintering.